Effect of dietary canthaxanthin and xanthophyll on growth, antioxidant capacity, body colour, and BCO2, CAT and SOD2 gene expression in Chinese soft‐shelled turtle (Pelodiscus sinensis). (8th November 2021) - Wang, Pei; Zhou, Xianwen; Xiong, Gang; Zeng, Dan; Ge, Lingrui; Luo, Zhijia; Qin, Qin; Wang, Xiaoqing; Hu, Yazhou
Abstract: This study was conducted to investigate the effects of single and mixed carotenoids dietary supplementation on the growth, immunity and skin colouration of Chinese soft‐shelled turtle. Six carotenoid‐supplemented diets (Diet 1/2/3/4/5/6) containing 0/50, 0/100, 0/120, 30/90, 60/60 and 90/30 mg/kg xanthophyll/canthaxanthin were prepared. A diet without carotenoid supplementation was used as the control. Turtles of the similar size (34.06 ± 0.56 g) were fed with these experimental diets for 72 days. The results showed that the turtles fed Diet 2 and Diet 4 had a better weight gain, specific growth and feed conversion ratio than those fed control diet ( p  < .05). Carotenoid supplementation improved antioxidant capacity and reduced lipid peroxidation in the serum and liver. The turtles in treatment diets showed higher skin redness and yellowness than those in control diet. Skin redness and yellowness were positively linearly related to canthaxanthin supplementation in feed, but the addition of xanthophyll achieved better skin yellowness. Moreover, dietary carotenoids increased the tissue carotenoid content and upregulated the expression of the enzyme β‐carotene oxygenase 2 ( BCO2 ), catalase ( CAT ) and superoxide dismutase 2 ( SOD2 ). According to the indexes of growth performance, antioxidant capacity and body colour, adding 100–120 mg/kg canthaxanthin or a 30/90–60/60 mg/kg ratio of xanthophyll/canthaxanthin in diets of Chinese soft‐shelled turtle was appropriate under the experimental conditions.